Spectrum allocation of cognitive wireless network based on immune clone selection optimization - CHAI Zheng-yi1; LIU Fang1 (Tongxin xuebao)
The spectrum sensing process was described based on WRAN.By analyzing physical connection of cognitive wireless network,the mathematical model of spectrum allocation was given,and then it was converted into a constrained optimization problem,whose goal was to maximum the profit of network.An immune clone selection algorithm was proposed to solve the problem,and the algorithm convergent with probability 1 was proved.Finally,the simulation experiments were done to test the algorithm.The results showed that compared with CSGC algorithm（color-sensitive graph coloring） and GA-SA（spectrum allocation based on genetic algorithm）,this algorithm could achieve maximization of network profits.Meanwhile,the system simulation results based on WRAN confirmed its effectiveness.